Indore city bus transport service (B) - Raghuram, G., 1955-; Sundaram, Satyam Shivam; Patni, Himanshu (London : Indian Institute of Management, Ahmedabad, 2010)
Towards the end of 1990s, mounting losses forced the Madhya Pradesh State Road Transport Corporation (MPSRTC), the sole provider of public transport in the central Indian state of Madhya Pradesh, to suspend its urban transport services. As a consequence, organized public transport services ceased to exist in Indore, the largest metropolitan city in the state. This void was filled by the Intermediate Public Transport System (IPTS), consisting of minibuses, tempos and auto rickshaws. In January 2004, 300 private minibuses, 150 tempos, and 10,000 auto rickshaws were plying in the city under the IPTS.Worried over the rapid growth in the number of personalized vehicles and the high levels of pollution and accidents in Indore, policy makers and administrators made several attempts to revive the public transport system in the city, but with little success. They believed that the lack of public transportation was the catalyst for the increase in personalized vehicles, pollution levels and the number of accidents in the city.In 2005, the Collector and District Magistrate of Indore, Vivek Aggarwal, decided to make another attempt to revive the city's public transport system. This attempt was conceived as a public-private partnership (PPP), and the Indore City Transport Service Limited (ICTSL) was the special purpose vehicle (SPV) created to run the system. The two cases, Indore City Transport Service (A) and Indore City Transport Service (B), discuss the complexity involved in planning, rolling out and running a public transport service in Indore on a sustainable basis.Case (B) discusses the challenges ICTSL faced during the growth and operation of the service. An unprecedented rise in crude oil prices, along with: i) an increase in the maintenance cost of buses, the price of new buses and bank interest, and ii) a decrease/ marginal increase in fare box revenue (as more commuters shifted to monthly passes) and advertisement revenue, depleted bus operators' margins substant
Originally published in Raghuram, G., Sundaram, S., & Patni, H. (2010). Indore City Bus Transport Service (B). CIPR0003(B). Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Urban transportation -- India -- Case studies; Transportation and state -- India -- Case studies; Bus lines -- India -- Case studies